2013
DOI: 10.1007/s00167-013-2764-9
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic repair of bucket-handle tears of the lateral meniscus

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 34 publications
1
38
3
4
Order By: Relevance
“…For comparison, other publications have reported even greater success in outcomes: Yilmaz et al 31 noted complete meniscal healing in all but one of 52 patients (mean age = 28.4 years) who underwent a combined inside-out and allinside technique for repair of bucket-handle meniscus tears at a mean 31.3-month follow-up. Ahn et al 32 retrospectively evaluated 13 patients with a median age of 20 years at a median 4.0 years follow-up after modified all-inside or combination all-inside/outside-in repair of lateral meniscus bucket-handle tears. The authors reported no reoperations during the follow-up period, no recurrence of mechanical locking symptoms, and significant improvements in Lysholm, HSS score, and Tegner activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, other publications have reported even greater success in outcomes: Yilmaz et al 31 noted complete meniscal healing in all but one of 52 patients (mean age = 28.4 years) who underwent a combined inside-out and allinside technique for repair of bucket-handle meniscus tears at a mean 31.3-month follow-up. Ahn et al 32 retrospectively evaluated 13 patients with a median age of 20 years at a median 4.0 years follow-up after modified all-inside or combination all-inside/outside-in repair of lateral meniscus bucket-handle tears. The authors reported no reoperations during the follow-up period, no recurrence of mechanical locking symptoms, and significant improvements in Lysholm, HSS score, and Tegner activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-nine (84%) of the patients in this cohort had concomitant ligament injuries, which may explain the outcome scores reported. Ahn et al 1 reported on outcomes after repair of isolated, displaced lateral meniscal bucket-handle tears in 13 patients at a median follow-up of 4 years. The authors reported full range of motion in all patients, a median Tegner score of 7, and a mean Lysholm of 94.6.…”
Section: Discussionmentioning
confidence: 99%
“…There is various nomenclature that describes this characteristic, such as recurrent subluxation of the lateral meniscus, popliteo-meniscal fascicle tear, hypermobile posterior horn of the lateral meniscus, and MRI negative bucket handle tear of the lateral meniscus3,4).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lateral meniscus is relatively loosely attached to the capsule that is interrupted by the popliteal hiatus, which allows it to be quite mobile. Therefore, the posterior horn of the lateral meniscus is susceptible to subluxation resulting in a displaced bucket handle tear3,4). We report a rare case of a child with a displaced bucket-handle tear of the lateral meniscus in the stable knee that healed spontaneously without any surgical procedures.…”
mentioning
confidence: 96%